The Impact of Market Orientation, Product Innovation, and Competitive Advantage on the Marketing Performance of Culinary Enterprises: Empirical Study in Kampar Regency, Indonesia - Irfandi, Nazmul; Halim, Edyanus Herman; Wijayanto, Gatot (Manunggal Halim Jaya, 2025)
In this study, the impact of product innovation and market orientation on the marketing performance and competitive advantage of micro-entrepreneurs in Kampar Regency's culinary industry will be examined. Additionally, this study assesses how competitive advantage influences marketing effectiveness by acting as a mediating factor between market orientation and product innovation. Tests of the direct and indirect effects between variables are conducted quantitatively using the SEM-PLS (Structural Equation Modeling - Partial Least Squares) analytical methodology. Questionnaires and interviews with micro-entrepreneurs in Kampar Regency's culinary industry were used to gather data. A total of 378 respondents were chosen as relevant samples using the purposeful sampling approach. The findings indicated that competitive advantage was significantly enhanced by market focus and product innovation. Furthermore, marketing performance was significantly improved by competitive advantage, product innovation, and market orientation. Additionally, the link between market orientation and product innovation on marketing success was shown to be reinforced by competitive advantage acting as a mediator.